E.U. paediatric MOG consortium consensus: Part 1 – Classification of clinical phenotypes of paediatric myelin oligodendrocyte glycoprotein antibody-associated disorders. (November 2020) - Bruijstens, Arlette L.; Lechner, Christian; Flet-Berliac, Lorraine; Deiva, Kumaran; Neuteboom, Rinze F.; Hemingway, Cheryl; Wassmer, Evangeline; ,; Mog consortium, E.U. paediatric; Bruijstens, Arlette L.; Wendel, Eva-Maria; Lechner, Christian; et al.
Abstract: Over the past few years, increasing interest in the role of autoantibodies against myelin oligodendrocyte glycoprotein (MOG-abs) as a new candidate biomarker in demyelinating central nervous system diseases has arisen. MOG-abs have now consistently been identified in a variety of demyelinating syndromes, with a predominance in paediatric patients. The clinical spectrum of these MOG-ab-associated disorders (MOGAD) is still expanding and differs between paediatric and adult patients. This first part of the Paediatric European Collaborative Consensus emphasises the diversity in clinical phenotypes associated with MOG-abs in paediatric patients and discusses these associated clinical phenotypes in detail. Typical MOGAD presentations consist of demyelinating syndromes, including acute disseminated encephalomyelitis (ADEM) in younger, and optic neuritis (ON) and/or transverse myelitis (TM) in older children. A proportion of patients experience a relapsing disease course, presenting as ADEM followed by one or multiple episode(s) of ON (ADEM-ON), multiphasic disseminated encephalomyelitis (MDEM), relapsing ON (RON) or relapsing neuromyelitis optica spectrum disorders (NMOSD)-like syndromes. More recently, the disease spectrum has been expanded with clinical and radiological phenotypes including encephalitis-like, leukodystrophy-like, and other non-classifiable presentations. This review concludes with recommendations following expert consensus on serologic testing for MOG-abs in paediatric patients, the presence of which has consequences for long-term monitoring, relapse risk, treatments, and for counselling of patient and families. Furthermore, we propose a clinical classification of paediatric MOGAD with clinical definitions and key features. These are operational and need to be tested, however essential for future paediatric MOGAD studies. Highlights: MOGAD include a diverse range of demyelinating and encephalitis-like phenotypes. ADEM in younger and ON and/or TM in older children comprise >90% of presentations. All children with demyelination/encephalitis and abnormal MRI need MOG-ab testing. We recommend an antibody-directed classification: MOG-ab-associated disorders. Followed by addition of the disease course and clinical phenotype.